'Where a lapse into English is invariably accepted': the use of L1 in language classrooms in England during the audio-visual period of the 1970s, viewed from a middle school perspective. (4th May 2019) - Michael Daniels, John
ABSTRACT: This paper draws on the literature and documents of the time audio-visual period in language classrooms of the 1970s in England, and the personal experience of the author as a French teacher for pupils aged nine to thirteen. The title quotation is taken from a questionnaire given to language teachers at a 1970s conference. During the 'revolutionary' audio-visual language period, language learning was introduced to primary-aged pupils and extended to older pupils of all abilities, involving a learning process described as 'the exposure of children to the second language in real-life situations which exclude the use of English'. The article looks at how, in the absence of translation and English explanations in audio-visual learning, the visual element became of central importance. There is evidence, however, that many teachers found it difficult to maintain exclusive use of the target language and found it necessary often to revert to English in their lessons, a response that detracted from the immersive nature of audio-visual learning and might ultimately be seen as one of the factors leading to the critical reports of Burstall (1970, 1974) and the abandonment of primary French learning in England at this time.